Role of obstetric Doppler in prediction of adverse perinatal outcome in intrauterine growth retardation - P., Chirtrarasan; S., Kanagarameswarakumaran (International Journal of Advances in Medicine, 2017)
Background: Objective of current study was to determine and compare accuracy of various Doppler parameters for perinatal outcome. Umbilical artery (UA), middle cerebral artery (MCA), and ductus venosus (DV) for predicting adverse perinatal outcome in patients of intrauterine growth retardation. Methods: 200 singleton pregnancies between 34 to 36 weeks of gestation complicated by intrauterine growth restriction were prospectively examined with Doppler ultrasound of the umbilical artery, middle cerebral artery and ductus venosus. Patients kept under surveillance till confinement. According to increasing severity of Doppler indices categorized the cases into six grades from grade 0 to grade 5. Results: Out of 200 cases, 169 were live born and 24 were neonatal death. There were 5 cases of intrauterine death of foetuses and 2 were still born. Out of the live born 32 had increased perinatal morbidity like poor APGAR score, development of necrotizing enterocolitis, hypoxic ischemic encephalopathy, meconium aspiration syndrome, hyperbilirubinemia, and prolonged admission in neonatal care unit for reasons like sepsis / birth asphyxia. Conclusions: Absent end diastolic flow (EDF) / reversal in umbilical artery had high positive predictive value in predicting adverse foetal outcome. Ductus venosus changes seem to be an ominous sign of a severely compromised foetus with poor perinatal outcome. Doppler investigation of the MCA, UA and DV plays an important role in monitoring the compromised foetuses and helps to determine the optimal time of delivery.